Cost of Achieving HbA1c Treatment Targets and Weight Loss Responses with Once-Weekly Semaglutide Versus Dulaglutide in the United States - Wilkinson, Lars (Diabetes Ther, 2018)
INTRODUCTION: The National Health and Nutrition Examination Surveys show that many people with type 2 diabetes (T2D) in the USA fail to achieve recommended treatment targets. In the SUSTAIN 7 randomized controlled trial, once-weekly semaglutide (0.5 and 1.0 mg) was superior to comparative doses of dulaglutide (0.75 and 1.5 mg) in reducing glycated hemoglobin (HbA1c) and body weight in people with T2D. The present study estimated the cost per patient achieving HbA1c treatment targets and weight loss responses with once-weekly semaglutide and dulaglutide in the USA. METHODS: Numbers needed to treat and annual cost per patient achieving HbA1c targets (including a triple composite endpoint of HbA1c < 7% without hypoglycemia and no weight gain) or weight loss responses were calculated on the basis of data from SUSTAIN 7 and the annual cost of treatment from a US healthcare payer perspective. RESULTS: More patients reached HbA1c targets with once-weekly semaglutide than with dulaglutide, and once-weekly semaglutide showed lower costs of control for all modeled endpoints. The cost per patient achieving the triple composite endpoint was USD 11,916 with once-weekly semaglutide 1.0 mg and USD 15,204 with dulaglutide 1.5 mg, representing a 28% larger cost with dulaglutide 1.5 mg. The cost of reaching the target was 68% larger with dulaglutide 0.75 mg versus once-weekly semaglutide 0.5 mg. For each patient achieving an HbA1c < 7%, the cost would be 18% larger with dulaglutide 1.5 mg than with once-weekly semaglutide 1.0 mg. CONCLUSIONS: The cost of bringing one patient to the triple composite endpoint of an HbA1c < 7% without hypoglycemia and no weight gain would be 28% and 68% higher with dulaglutide 1.5 mg relative to once-weekly semaglutide 1.0 mg and dulaglutide 0.75 mg relative to once-weekly semaglutide 0.5 mg, respectively. Once-weekly semaglutide therefore provides better value for money than dulaglutide for the treatment of people with T2D in the USA. FUNDING: Novo Nordisk A/S.